1990
DOI: 10.1038/346335a0
|View full text |Cite
|
Sign up to set email alerts
|

Movement of internalized ligand–receptor complexes along a continuous endosomal reticulum

Abstract: Complexes of cell-surface receptors and their ligands are commonly internalized by endocytosis and enter a prelysosomal endosomal pathway for further processing. Fluorescence microscopy and video recording of living cells to trace the passage of ligand-receptor complexes has identified the endosomal compartment as an extensive network of tubular cisternae. Endocytosed material entering this reticulum enters discrete swellings, identified as multivesicular bodies by electron microscopy, which move along the ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
217
3
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 413 publications
(250 citation statements)
references
References 23 publications
29
217
3
1
Order By: Relevance
“…These tubules have no attached ribosomes, but they are in continuity with the rough endoplasmic reticulum (32). The extensive network of tubules and vesicles that transport the virions from one part of the cell to another is also consistent with recently described cisternal compartments within intracellular transport pathways that include branching tubular elements that can be several micrometers long (33). Specifically regarding SV40 virions, it has been demonstrated that, while avoiding lysosomal degradation, they take advantage of a retrograde endocytic pathway that leads to the RER and from there to the nucleus.…”
Section: Discussionsupporting
confidence: 84%
“…These tubules have no attached ribosomes, but they are in continuity with the rough endoplasmic reticulum (32). The extensive network of tubules and vesicles that transport the virions from one part of the cell to another is also consistent with recently described cisternal compartments within intracellular transport pathways that include branching tubular elements that can be several micrometers long (33). Specifically regarding SV40 virions, it has been demonstrated that, while avoiding lysosomal degradation, they take advantage of a retrograde endocytic pathway that leads to the RER and from there to the nucleus.…”
Section: Discussionsupporting
confidence: 84%
“…Under the conditions of most rapid quenching of intracellular acidic pH, i.e. bafilomycin A1 plus monensin, cells are protected for more than 1 h. Cell ligands such as EGF or LDL enter early endosomal compartments within few minutes and move to late endosomal compartments within 20-30 min [27,28]. Based on these data, the present results indicate that LF undergoes the low pH-dependent step of its cell intoxication process in late endosomal compartments.…”
Section: Resultssupporting
confidence: 55%
“…Secondly, the early endosome network is not morphologically well characterized. Those studies that have been performed indicate that what is commonly referred to as the early endosome is in fact highly complex and heterogeneous and dependent on cell type (Marsh et al, 1986;Hopkins et al, 1990;Tooze and Hollinshead, 1991). In most cell types, this early endosome network is composed of at least two separate compartments, the sorting endosome and the recycling compartment, which are morphologically and functionally distinct (Dunn et al, 1989;Presley et al, 1993;Marsh et al, 1995).…”
Section: Discussionmentioning
confidence: 99%